Processing of date palm kernel (DPK) for production of edible jam - Mirghani, Mohamed Elwathig Saeed; Al-Mamun, Abdullah; Daoud, Jamal Ibrahim; Mustafa, Simma Mahirah (INSI Publications, 2012)
Powdered date palm (Phoenix dactylifera) kernel (DPK) was used to produce edible jam. Saccharose, pectin, water, citric acid, ascorbic acid and Gum Arabic were added to the jam. Design Expert software was used to determine the optimum amount of the ingredients for the DPK jam. The design showed that there were ten variations of jams to be produced according to the content of different materials where the parameters such as amount of saccharose, pectin and dietary fiber from Gum Arabic were varied to give the best acceptability of the DPK jam samples. The jam samples produced were evaluated in terms of the sensory evaluation which includes taste, texture, aroma, appearance and overall acceptability by the panelist selected from students of Biochemical- Biotechnology Engineering, International Islamic University Malaysia. The samples were evaluated based on a five point hedonic scale, where zero (0.0) represented “disliked extremely” and four (4.0) represented “liked extremely”. All the data were analyzed by using Microsoft Excel spreadsheet. The results showed that 60% of panelists accept (> 3.1/4) the product while the others 40 % moderately accept (2.55 – 2.64/4) the DPK jam samples. The average of overall acceptability is 2.98/4. This study is the outcome of the research done to find the acceptability of the production of DPK jams.